Situating The Self: Overcoming Subjection and Subjectivity in Toni Morrison’s Sula - Ramesh, Dr. T.S. (citeus, 2018)
Individual Autonomy is a prominent feature of women writers. It plans to advance a dream of self-governing self as basically autonomous and independent, a dream that precludes the inevitable connectedness from securing selves and the way that their inundation in systems of connections frames their wants, yearnings, to be sure their extremely personalities. As such, what is denied is that the self is basically social. Toni Morrison, an Afro-American woman writer, works strenuously to get autonomous self to her female protagonist. In her novels, she clearly describes the life of African-American women in white dominated in American society. Combining the aims of African-American Freedom Movement and Woman’s Liberation, she produces literature which is indisputably black. In this research article, Toni Morrison’s famous novel Sula has been discussed through two chief characters, Nel and Sula. The novelist tries to overcome racial boundaries in order to gain animated self with striking balance. To be specific, the chief protagonists of Toni Morrison tend to find expression amidst their sullen, irritable, and dangerously regressive existence, to find dependence of their own, complaisant and reliant beings.